Male-specific repeats in wild Bovidae - Cabelova, Katerina; Kubickova, Svatava; Cernohorska, Halina; Rubes, Jiri (Journal of Applied Genetics, 2012)
In this study, we investigated repetitive sequences localized on Y chromosomes. Repetitive DNA sequences represent a substantial part of the eukaryotic genome and, among them, a large portion comprises sequences repeated in tandem. Efficient and rapid isolation of repeat units is possible due to a laser microdissection technique used for Y chromosome separation, followed by polymerase chain reaction (PCR), cloning, and sequence analysis. We applied the derived repeat units to members of nine tribes within the Bovidae. Apart from the Y chromosomes of Bos taurus and Bubalus bubalis, where we used known sequences of repetition, the derived sequences were used as probes for fluorescent in situ cross-hybridization to members of the nine tribes of the Bovidae. We investigated the distribution of repeat units within the tribes and their localization on the Y chromosome. Sharing of sequence variants would indicate common descent, while the rapid horizontal evolution should allow discrimination between closely related species or subspecies.
Keywords: Cattle; Animals; Y Chromosome; skot; Base Sequence; Repetitive Sequences, Nucleic Acid; Fluorescent Dyes; druhová specificita; Species Specificity; laserová záchytná mikrodisekce; molekulární evoluce; metafáze; fluorescenční barviva; repetitivní sekvence nukleových kyselin; Evolution, Molecular; Metaphase; Phylogeny; Sex Factors; Genetics, Population; Male; populační genetika; sexuální faktory; Sequence Alignment; sekvence nukleotidů; Sequence Analysis, DNA; hybridizace in situ fluorescenční; zvířata; mužské pohlaví; sekvenční seřazení; sekvenční analýza DNA; fylogeneze; In Situ Hybridization, Fluorescence; Laser Capture Microdissection; chromozom Y